The Effect of HbA1c on Cognitive Functions in Children with Type 1 Diabetes Mellitus - Hasanova Nafisa Okilovna; Ochilova Melioy Tojiboevna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Annotation: The association between diabetes mellitus and cognitive impairment was first hypothesized in 1922. In recent years, complications of diabetes that arise from the central nervous system have been studied more extensively. Clinically significant cognitive dysfunction leads to impaired work capacity and social adaptation, as well as a deterioration in the quality of life of patients with diabetes mellitus [1].